Features of development of maximum and explosive strength in weightlifting groups of sports improvement and higher sports skill - Pogrebnyak, S. A.; Nikulin, I. N.; Sobyanin, F. I.; Belousova, I. N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to experimentally test the method of strength training of weightlifters in the groups of sports improvement and higher sportsmanship using the static-dynamic method and plyometric exercises.